Design and fabrication of solar chimney - Yong, Weng Kheong. (Universiti Malaysia Sarawak, UNIMAS, 2006)
Non renewable energy resources will soon be exhausted, consequently leading to the world energy crisis. As this happens, non renewable e nergy is being replaced by renewable energy resources. This work presents the design, fabrication and performance analysis of a solar chimney power generator. Solar Chimney power generator utilize hot air rise concept in power generation. The design consis ts of a chimney tower built on top of a circular solar collector . These two structures are connected via a curved cave called the chimney support. Below t he solar collector lays the heat absorber plates and water tubes for heat storage which is later used for night operation. An air flow director is placed below the chimney to direct the air upward which then turns the electric generator in the chimney. Solar chimney is designed to generate electric power 24 hours a day based on the hot air rise concept. Th e overall performance of the solar chimney is studied in this project. In this project, the fabrication method was employed. The performance of a solar chimney is dependent on the sun radiation, solar collector’s size, collector glass’s transparency and gr ound type. The night operation performance is influenced by the ground properties and water tube size. The fabrication of solar chimney involves manufacturing a structure of 4.2m in diameter and 3m in height. With this prototype design it is hope 1W of ene rgy will be obtained.